Upregulation of PGC-1α Attenuates Oxygen-Glucose Deprivation-Induced Hippocampal Neuronal Injury - Bin Han; Hui Zhao; Xingji Gong; Jinping Sun; Song Chi; Tao Liu; Anmu Xie (Neural Plasticity)
Hippocampal neuronal damage likely underlies cognitive impairment in vascular dementia (VaD). PPARγ coactivator-1α (PGC-1α) is a master regulator of mitochondrial biogenesis. However, the role and the precise mechanism of how PGC-1α alleviates hippocampal neuronal injury remain unknown. To address this question, HT-22 cells, an immortalized hippocampal neuron cell line, with or without PGC-1α overexpression were subjected to oxygen-glucose deprivation (OGD), which mimics the circumstance of chronic cerebral hypoperfusion in VaD. After OGD, cell viability was assessed using the MTS assay. The mitochondrial function and reactive oxygen species (ROS) were both detected. ChIP-Seq analysis was employed to discover the underlying molecular mechanism of PGC-1α-mediated neuroprotective effects. Our results showed that mitochondrial membrane potentials were increased and ROS production was decreased in PGC-1α overexpressing cells, which increased cell viability. The further bioinformatics analysis from ChIP-Seq data indicated that PGC-1α may participate in the regulation of apoptosis, autophagy, and mitophagy pathways in HT-22 cells. We found that PGC-1α promoted the LC3-II formation and reduced the neuronal apoptosis determined by TUNEL staining. In addition, PGC-1α upregulated the expressions of mitochondrial antioxidants, including SOD2, Trx2, and Prx3. In summary, our findings indicate that PGC-1α may attenuate OGD-induced hippocampal neuronal damage by regulating multiple mechanisms, like autophagy and mitochondrial function. Thus, PGC-1α may be a potential therapeutic target for hippocampal damage associated with cognitive impairment.